IDENTIFICATION OF FACULTY PERCEPTIONS ABOUT THEIR LEARNING ENVIRONMENT AND COMPARISON BASED ON CURRICULA AND GENDER - Rehmah Sarfraz; Faiza Kiran; Memoona Mansoor; Rahila Yasmin; Komel Zulfiqar (Pakistan Armed Forces Medical Journal, 2019)
Objective: To identify faculty perceptions about their learning environment and compare these based on curricula and gender.